1973
DOI: 10.1021/bi00726a002
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and structure determination of the fluorescent base from bovine liver phenylalanine transfer ribonucleic acid

Abstract: Calf and beef liver tRNAphe were obtained by fractionation of calf and beef tRNA on BD-cellulose columns and selected regions were further purified by hydroxylapatite chromatography. The tRNAphe was then incubated at pH to the following abbreviations: structure A: imGua (for l,.V--isopropeno-3-methylguanine); structure B: Y-imGua (it so happens that the branched butyrate side chain looks like the letter Y, and hence the original letter can be retained as a modifier), The respective nucleosides become imG and Y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0

Year Published

1974
1974
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(47 citation statements)
references
References 22 publications
3
44
0
Order By: Relevance
“…In fact, OHyW was detected in A. . Peroxywybutosine (o2yW), which has been identified in mammalian tRNA Phe (22,23), was not present in our preparation, similar to a previous report (8). C, biosynthetic pathway of OHyW.…”
Section: Identification Of Tyw5 Responsible For Ohyw Formation-supporting
confidence: 90%
“…In fact, OHyW was detected in A. . Peroxywybutosine (o2yW), which has been identified in mammalian tRNA Phe (22,23), was not present in our preparation, similar to a previous report (8). C, biosynthetic pathway of OHyW.…”
Section: Identification Of Tyw5 Responsible For Ohyw Formation-supporting
confidence: 90%
“…We therefore conclude that this calf liver tRNAPhe contains only peroxy-Y. This result can be explained by the observation of Blomstein et al [7] who found that beef liver tRNAPhe also contains only peroxy-Y. Our result therefore can be due to the fact that the calf liver tRNAPhe purchased from Boehringer-Mannheim may have been extracted from older calves than the calf liver tRNAPhe prepared by Blomstein et al [7] where the maturation of Y into peroxy-Y was not completely achieved.…”
Section: Methodssupporting
confidence: 77%
“…The fluorescent base adjacent to the 3' end of the anticodon was previously found in calf liver tRNAPhe to be a mixture of 9% peroxy-Y base and 10% Y base [7]. With the calf liver tRNAPhe we used in this work, we obtained only one spot which had an RF similar to that described for peroxy-Y.…”
Section: Methodsmentioning
confidence: 55%
See 1 more Smart Citation
“…The chemical nature of these modifications ranges from the simple introduction of methyl groups on one hand to hypermodified nucleosides such as wybutosine (Blobstein et al 1973) or agmatidine (Mandal et al 2010) on the other hand. To date, more than 100 chemically different modifications have been described for tRNA nucleotides (Rozenski et al 1999).…”
Section: Introductionmentioning
confidence: 99%